Simulation of Diffusion Mechanism and Dynamics in Alumina Liquid under Pressure - Nguyen, Thi Thanh Ha (H. : ĐHQGHN, 2017)
Diffusion mechanism and dynamics in Al2O3 liquidhave been studied via molecular dynamics simulation. Six models with different density and at temperature of 3000 K have been used to study the atomistic mechanism governing the process of the bond-breaking and bond-reformation (the transition AlOx®AlOx+1 and AlOx®AlOx-1). Calculation shows that the diffusion of particle Al is realized via the transition AlOx®AlOx±1 and the rate of transition AlOx®AlOx±1 monotonously increases with pressure. When applying pressure to liquid the diffusion mechanism changes from strong localization of transitions SiOx®SiOx±1 in the sample at ambient pressure to uniform distribution transitions SiOx®SiOx±1 in high-pressure sample. Furthermore, we find two distinguish regions with quite different coordination environment where the rate of transitions SiOx®SiOx±1 strongly differs from each other. The result obtained clearly evidences the spatially heterogeneous dynamics in the liquid.